The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.imbio.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a panel of cross-reactive monoclonal antibodies generated using H1N1 influenza virus

Abstract: To characterize the antigenic epitopes of the hemagglutinin (HA) protein of H1N1 influenza virus, a panel consisting of 84 clones of murine monoclonal antibodies (mAbs) were generated using the HA proteins from the 2009 pandemic H1N1 vaccine lysate and the seasonal influenza H1N1(A1) vaccines. Thirty-three (39%) of the 84 mAbs were found to be strain-specific, and 6 (7%) of the 84 mAbs were subtype-specific. Twenty (24%) of the 84 mAbs recognized the common HA epitopes shared by 2009 pandemic H1N1, seasonal A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…7 Heterophilic antibody interference has been reported for many tumor markers (alpha-fetoprotein, CA125, beta-human chorionic gonadotropin, squamous cell carcinoma antigen, and prostate-specific antigen), hormones (thyrotrophic hormone and estradiol), and infection markers (influenza and human hepatitis B antigen) using immunochromatography assays. 6,[8][9][10] Commercial quantitative methods have been improved to reduce heterophilic interference by removing the Fc portion and avoid the binding of heterophilic antibodies; this can also be achieved by adding a HAMA blocker or adsorbing the heterophilic antibodies using IgG from the same animal or serum, as a secondary antibody. In comparison, most immunochromatography assays, including PCT-Q ® , use whole immunoglobulins, which result in more frequent heterophilic interference.…”
Section: Discussionmentioning
confidence: 99%
“…7 Heterophilic antibody interference has been reported for many tumor markers (alpha-fetoprotein, CA125, beta-human chorionic gonadotropin, squamous cell carcinoma antigen, and prostate-specific antigen), hormones (thyrotrophic hormone and estradiol), and infection markers (influenza and human hepatitis B antigen) using immunochromatography assays. 6,[8][9][10] Commercial quantitative methods have been improved to reduce heterophilic interference by removing the Fc portion and avoid the binding of heterophilic antibodies; this can also be achieved by adding a HAMA blocker or adsorbing the heterophilic antibodies using IgG from the same animal or serum, as a secondary antibody. In comparison, most immunochromatography assays, including PCT-Q ® , use whole immunoglobulins, which result in more frequent heterophilic interference.…”
Section: Discussionmentioning
confidence: 99%
“…mAbs against the H1N1 influenza virus HA protein, including H1-84mAb, were prepared in our laboratory. The titre of the antibody was determined using the indirect ELISA method, and the reactivity of the antibody with the HA antigen was determined by western blotting (8). It has been previously determined that H1-84mAb binds to a nine-peptide linear epitope (191-LVLWGIHHP-199) on HA (12).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, 84 monoclonal antibodies (mAbs) against hemagglutinin (HA) were prepared. When identifying their characteristics, it was revealed that the H1-84mAb not only binds to the HA antigen, but also cross-reacts with human brain tissue, suggesting that H1N1 influenza virus HA and human brain tissue have a heterophilic antigen (8). Heterophilic antigens are a class of common antigens that are unrelated between species, and exist in humans, animals and microorganisms (9).…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments were approved by the Institutional Animal Care and Use Committee of Shaanxi Provincial People's Hospital (Shaanxi, Xi'an). The preparation of mAbs has been reported previously 7 .…”
Section: Preparation and Identification Of The Mabsmentioning
confidence: 99%
“…The authors proposed that these cross-reactive antibodies are associated with immune complex-mediated disease after H1N1 infection. 6 To investigate the possible effect of antibodies against H1N1 influenza virus, we used the type A H1N1 virus vaccine as an antigen and generated 84 mouse monoclonal antibodies (mAbs), and found that some mAbs could cross-react with human tissues 7 . In the present study, we further explored the topography of the immunoreactivity of the antibodies in pancreatic tissues.…”
Section: Introductionmentioning
confidence: 99%